2010
DOI: 10.4037/ajcc2011331
|View full text |Cite
|
Sign up to set email alerts
|

Medication Errors in Critically Ill Adults: A Review of Direct Observation Evidence

Abstract: Objective To systematically review clinical evidence gathered by direct observation of medication errors in adult patients in intensive care units. Methods Articles published between 1985 and 2008 in Englishlanguage journals indexed by the Cumulative Index for Nursing and Allied Health Literature and PUBMED were searched for studies on medication errors made by intensive care unit nurses. Studies in which errors were detected via direct observation were included. Results Six studies met the inclusion criteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 39 publications
(72 reference statements)
3
36
0
4
Order By: Relevance
“…Pesquisa que avaliou a incidência relatada, causas e relatórios de erros de medicação em unidades de terapia intensiva (UTI) e enfermarias de hospitais de ensino da Jordânia em 2010, mostrou que a média da incidência de erros de medicação para toda a amostra foi de 35%, sendo 36,4% em UTI e 33,8% nas enfermarias (3) .No que diz respeito, especificamente, aos erros de administração de medicamentos em ambientes de cuidados de saúde, as taxas chegam a atingir 59,1% do total das oportunidades de erro (4) e nas unidades de cuidados críticos alcançam72,5% (5) . Investigação realizada com enfermeiros de Unidades de Cuidados Intensivos Neonatais e Unidades Neonatais de cinco hospitais de ensino de ShahidBeheshti (Irã), revelou que 37,8% dos participantes haviam cometido de um a dois erros de medicação nos últimos seis meses.…”
Section: Introductionunclassified
“…Pesquisa que avaliou a incidência relatada, causas e relatórios de erros de medicação em unidades de terapia intensiva (UTI) e enfermarias de hospitais de ensino da Jordânia em 2010, mostrou que a média da incidência de erros de medicação para toda a amostra foi de 35%, sendo 36,4% em UTI e 33,8% nas enfermarias (3) .No que diz respeito, especificamente, aos erros de administração de medicamentos em ambientes de cuidados de saúde, as taxas chegam a atingir 59,1% do total das oportunidades de erro (4) e nas unidades de cuidados críticos alcançam72,5% (5) . Investigação realizada com enfermeiros de Unidades de Cuidados Intensivos Neonatais e Unidades Neonatais de cinco hospitais de ensino de ShahidBeheshti (Irã), revelou que 37,8% dos participantes haviam cometido de um a dois erros de medicação nos últimos seis meses.…”
Section: Introductionunclassified
“…Licensed registered nurses who worked in an adult intensive care unit (ICU) as direct patient caregivers comprised the study sample. ICUs were chosen because high rates of errors are reported on nursing units that provide acute care for critically ill patients, such as intensive care units (Brunsveld-Reinders, Arbous, De Vos, & De Jonge, 2016;Landrigan et al, 2004), and critically ill patients experience higher rates of adverse events and errors than other patient populations (Balas, Scott, & Rogers, 2006;Kiekkas, Karga, Lemonidou, Aretha, Karanikolas, 2011).…”
mentioning
confidence: 99%
“…In the current study about half of nurses reported that the lack of safety guidelines and training program at their work place considered obstacles facing safe chemotherapy administration. This is confirmed by research Kikase (2011) [33] study findings revealed that incompetency in practice and poor level of knowledge of nurses ' administering chemotherapy. Also this finding in line with Orujulus (2016) [34] study findings which revealed that slightly more than half and one of nurses reported that lack of safety guidelines and training programs at their workplaces respectively.…”
Section: Similar To Findings Of Abbasy (2013 ) [21] Gauski (2016)mentioning
confidence: 52%